Building a Resilient Change-Oriented Virtual Leadership Framework for the Higher Education Sector: A Narrative Review - Yew-Chee Chew; Siti Rohaida Mohamed Zainal (Journal of Higher Education Policy and Leadership Studies, 2022)
The Covid-19 pandemic has forced many institutions to convert to the virtual work model in the blink of an eye, protecting the health of students and employees while maintaining digital productivity. Many pedagogues in higher education institutions reported that their remote work experience during the pandemic lacked leadership support and training, especially in the areas of information technology competencies. This issue clearly indicates that leadership and management were unprepared to deal with virtual transformation when the dynamic external influence calls for a virtual change. This paper uses a narrative review method to explore the historical context of telecommuting and critically review the development of virtual leadership literature in higher education, which finally leads to formation of a comprehensive virtual leadership conceptual framework that could be utilised in future research.